GaN‐on‐silicon high electron mobility transistors with blocking voltage of 3 kV. Issue 19 (4th September 2015) - Herbecq, N.; Roch‐Jeune, I.; Linge, A.; Grimbert, B.; Zegaoui, M.; Medjdoub, F.
Abstract : A three‐terminal breakdown voltage over 3 kV is reported on AlGaN/GaN high‐electron‐mobility transistors (HEMTs) grown on silicon (Si) (111) substrate with a buffer thickness of 5.5 µm. The breakdown voltage of the 1.5 × 50 μm 2 devices has been improved by more than 200% by applying a local substrate removal all around the drain of the transistors in order to suppress the parasitic substrate conduction phenomenon. This establishes a new record breakdown voltage for GaN‐on‐silicon lateral power devices while maintaining a low specific on‐resistance of about 10 mΩ · cm 2 .